2018
DOI: 10.1016/j.tim.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Surface Area to Volume Ratio: A Natural Variable for Bacterial Morphogenesis

Abstract: An immediately observable feature of bacteria is that cell size and shape are remarkably constant and characteristic for a given species in a particular condition, but vary quantitatively with physiological parameters such as growth rate, indicating both genetic and environmental regulation. However, despite decades of research, the molecular mechanisms underlying bacterial morphogenesis have remained incompletely characterized. We recently demonstrated that a wide range of bacterial species exhibit a robust s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 66 publications
6
100
0
Order By: Relevance
“…In the bionic world, VSR could be one dominating factor in the shapes and sizes of cells [13], [14]. A cell receives nutrition from the outside environment through the cell membrane; the surface area represents the cell's efficiency in absorbing nutrition, and its volume represents the amount of nutrition needed.…”
Section: B Non-detectable Subspace Segmentationmentioning
confidence: 99%
“…In the bionic world, VSR could be one dominating factor in the shapes and sizes of cells [13], [14]. A cell receives nutrition from the outside environment through the cell membrane; the surface area represents the cell's efficiency in absorbing nutrition, and its volume represents the amount of nutrition needed.…”
Section: B Non-detectable Subspace Segmentationmentioning
confidence: 99%
“…We next evaluated whether specific changes in fundamental cellular features occurring during cell fusion were responsible for YAP1 inactivation and transcriptional reprogramming. Changes in shape are known to be governed by alterations in both volume and surface area (SA) (Harris and Theriot, 2018;Okie, 2013). Importantly, recent work has shown that YAP1 activity and cellular localization is altered through variations in volume and/or SA (Hong et al, 2017;Low et al, 2014;Nardone et al, 2017;Perez Gonzalez et al, 2018;Cai et al, 2019).…”
Section: Cell Fusion Promotes Increased Endocytosis Altering Plasma Mmentioning
confidence: 99%
“…Phase-contrast images of the bacteria are taken every 5 min and cells' length is extracted as described in Materials and Methods and Figure 1A. Figure 1B shows single cell growth rates, which we define as a rate of relative elongation of an exponentially growing bacterium 8,43 , of the cells grown on different surfaces. The growth rate observed is independent on the surface attachment, and, when we average the values obtain for the 6 different surfaces in Figure 1B, equals (0.0071 ± 0.0044 min −1 ) .…”
Section: Growth Rate and Morphology Of Bacteria Do Not Dependent On Tmentioning
confidence: 99%